An experimental design to extract more information from MS-based histone studies. (15th September 2021) - De Clerck, Laura; Willems, Sander; Daled, Simon; Van Puyvelde, Bart; Verhelst, Sigrid; Corveleyn, Laura; Deforce, Dieter; Dhaenens, Maarten
Abstract : Enzymatic treatment of a commercial histone extract as a quantify-first strategy allows isolating ion populations of interest that currently remain in the dark. Abstract : Histone-based chromatin organization paved the way for eukaryotic genome complexity. Because of their key role in information management, the histone posttranslational modifications (hPTM), which mediate their function, have evolved into an alphabet that has more letters than there are amino acids, together making up the "histone code". The resulting combinatorial complexity is manifold higher than what is usually encountered in proteomics. Consequently, a considerably bigger part of the acquired MSMS spectra remains unannotated to date. Adapted search parameters can dig deeper into the dark histone ion space, but the lack of false discovery rate (FDR) control and the high level of ambiguity when searching combinatorial PTMs makes it very hard to assess whether the newly assigned ions are informative. Therefore, we propose an easily adoptable time-lapse enzymatic deacetylation (HDAC1) of a commercial histone extract as a quantify-first strategy that allows isolating ion populations of interest, when studying e.g. acetylation on histones, that currently remain in the dark. By adapting search parameters to study potential issues in sample preparation, data acquisition and data analysis, we stepwise managed to double the portion of annotated precursors of interest from 10.5% to 21.6%. This strategy is intended to make up for the lack of validated FDR control and has led to several adaptations of our current workflow that will reduce the portion of the dark histone ion space in the future. Finally, this strategy can be applied with any enzyme targeting a modification of interest.